Antibiotic prescribing practices in general surgery: a mixed methods quality improvement project. Issue 3 (September 2021) - Lamb, Georgia; Phillips, Georgina; Charani, Esmita; Holmes, Alison; Satta, Giovanni
Summary: Background: A single pre-operative antibiotic dose provides optimal prophylaxis against surgical site infection (SSI), but significant variability persists in adherence to prophylaxis guidelines. We describe a quality improvement project aiming to improve guideline-driven antibiotic prescribing within surgical teams at a tertiary hospital. Methods: Face-to-face interviews with surgical teams and anonymous surveys of senior surgeons and anaesthetists were used to collect qualitative data on the perceptions and attitudes of prescribers. This informed intervention development, including a daily ward-round checklist using the acronymous 'ABBDDOMM', from A (antibiotics) to M (microbiology), combined with education and heightened guideline accessibility. A first audit cycle was performed for patients undergoing intra-abdominal surgery during a two-month period (cycle one). Post-implementation data were collected 12 months later (cycle two). Findings: Interviews provided insight into common themes and barriers surrounding antibiotic prescribing, whilst surveys explored future solutions to these barriers. In cycle one, 100/205 (48.8%) patients received extended antibiotics beyond the single-dose prophylaxis. Following intervention, only 41/138 (29.7%) patients received extended antibiotic courses, demonstrating a 21.5% reduction in prolonged antibiotics (P<0.0005). In cycle one, 107/205 patients (52.2%) received antibiotics compliant with Trust Guidelines, compared to 80/138 (58.0%) in cycle two. Conclusion: Our proposed checklist, alongside antimicrobial stewardship education, prompts daily review of important patient parameters and results to significantly reduce inappropriate post-operative antibiotic prescribing. Promoting the sustained use of similar checklists by junior doctors and focusing on measures to improve uptake of pre-operative induction antibiotic guidelines is required to achieve further benefits.